Optical polarization in biomedical applications - Tuchin, Valery V. (Springer, 2006)
Optical Polarization in Biomedical Applications introduces key developments in optical polarization methods for quantitative studies of tissues, while presenting the theory of polarization transfer in a random medium as a basis for the quantitative description of polarized light interaction with tissues. This theory uses the modified transfer equation for Stokes parameters and predicts the polarization structure of multiple scattered optical fields. The backscattering polarization matrices (Jones matrix and Mueller matrix) important for noninvasive medical diagnostic are introduced. The text also describes a number of diagnostic techniques such as CW polarization imaging and spectroscopy, polarization microscopy and cytometry. As a new tool for medical diagnosis, optical coherent polarization tomography is analyzed. The monograph also covers a range of biomedical applications, among them cataract and glaucoma diagnostics, glucose sensing, and the detection of bacteria. Tissue structure and optical models - Polarized light interactions with weakly scattering media - Polarized light interactions with strongly scattering media - Polarization properties of tissues and phantoms - Polarization-dependent interference of multiply scattered light - Decay of light polarization in random multiple scattering media - Degree of polarization in laser speckles from turbid media - Monte Carlo modeling of polarization propagation - Polarization-sensitive optical coherence tomography - Biomedical diagnostics and imaging.